Pengaruh Konsep Diri dan Berpikir Positif terhadap Prestasi Belajar Matematika Siswa - Yuan Andinny (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2013)
This study aims to investigate the influence of self-concept on academic achievement, the influence of positive thinking on learning achievement as well as the influence of self-concept and positive thinking to mathematics achievement. The method used was a survey method. Population targeted in this study were all students of class XI SMK State Citra, Depok. Samples were taken by simple random sampling technique, as many as 35 students. The research instrument consisted of 2 kinds of mathematics achievement (test scores), self-concept and positive thinking (a questionnaire). Data were analyzed by multiple regression correlation techniques. Hypothesis testing results show that there is significant self-concept on mathematics achievement, there is the influence of positive thinking on mathematics achievement, and there is the influence of self-concept and positive thinking together on mathematics achievement.